Everyday life - "Gifford, Clive" (Kingfisher Publications, London, 2000)
Surveys the development of technology in the modern world, from air travel to genetic engineering, and looks at possible future developments, showing how technology has changed our everyday life today and is likely to affect our lives in the near future.